Female Sex and Brain-Selective Estrogen Benefit α-Synuclein Tetramerization and the PD-like Motor Syndrome in 3K Transgenic Mice - Rajsombath, Molly M. (J Neurosci, 2019)
Many studies report a higher risk for Parkinson's disease (PD) and younger age of onset in men. This, and the fact that the neuropathological process underlying PD symptoms may begin before menopause, suggests that estrogen-based hormone therapy could modify this higher risk in males. However, the effects of female sex or estrogen on α-synuclein (αS) homeostasis and related PD neuropathology remain unknown. Here, we used an αS tetramer-abrogating mouse model of PD (3K) that amplifies the familial E46K PD mutation to investigate the effects of female sex and brain-selective estrogen treatment on αS tetramerization and solubility, formation of vesicle-rich αS(+) aggregates, dopaminergic and cortical fiber integrity, and associated motor deficits. In male 3K mice, the motor phenotype became apparent at ∼10 weeks and increased to age 6 months, paralleled by PD-like neuropathology, whereas 3K females showed a significant delay in onset. At 6 months, this beneficial phenotypic effect in 3K females was associated with a higher αS tetramer-to-monomer ratio and less decrease in dopaminergic and cortical fiber length and quantity. Brain-selective estrogen treatment in symptomatic 3K mice significantly increased the tetramer-to-monomer ratio, turnover by autophagy of aggregate-prone monomers, and neurite complexity of surviving DAergic and cortical neurons, in parallel with benefits in motor performance. Our findings support an upstream role for αS tetramer loss in PD phenotypes and a role for estrogen in mitigating PD-like neuropathology in vivo. Brain-selective estrogen therapy may be useful in delaying or reducing PD symptoms in men and postmenopausal women. SIGNIFICANCE STATEMENT The mechanisms responsible for the male-to-female preponderance in Parkinson's disease (PD) are not well understood yet important for treatment efficacy. We previously showed that abrogating native α-synuclein (αS) tetramers produces a close PD model, including dopaminergic and cortical fiber loss and a progressive motor disorder responsive to l-DOPA. Here, we analyzed sex and use 10b-17β-dihydroxyestra-1,4-dien-3-one treatment of symptomatic 3K males, and demonstrate that the beneficial effects of female sex on PD-like neuropathology can be reinstated by elevating estrogen in the male brain. The study provides evidence that 17β-estradiol restores the tetramer-to-monomer ratio by autophagy turnover of excess αS monomers, vesicle and fiber integrity in brain regions critically involved in motor behavior. These data provide the basis for understanding sex differences in αS homeostasis and the development of therapeutic approaches to treating men and postmenopausal women with PD.